Persisting mental health problems among AIDS-orphaned children in South Africa - Cluver, L.; Orkin, M.; Gardner, F.; Boyes, Mark (Wiley-Blackwell Publishing Ltd, 2012)
Background: By 2008, 12 million children in sub-Saharan Africa were orphaned by AIDS. Cross-sectional studies show psychological problems for AIDS-orphaned children, but until now no longitudinal study has explored enduring psychological effects of AIDS-orphanhood in the developing world. Methods: A 4-year longitudinal follow-up of AIDS-orphaned children with control groups of other orphans and non-orphans. 1021 children (M = 13.4 years, 50% female, 98% isiXhosa-speaking) were interviewed in 2005 and followed up in 2009 with 71% retention (49% female, M = 16.9 years), in poor urban South African settlements. Children were interviewed using sociodemographic questionnaires and well-validated standardised scales for assessing depression, anxiety, and post-traumatic stress. Data were analysed using mixed-design ANOVA and backward-stepping regression. Results: AIDS-orphaned children showed higher depression, anxiety, and post-traumatic stress disorder (PTSD) scores in both 2005 and 2009 when compared with other-orphans and non-orphans. Backward-stepping regression, controlling for baseline mental health, and sociodemographic cofactors such as age, gender, and type of bereavement, revealed that being AIDS-orphaned in 2005 was associated with depression, anxiety, and PTSD scores in 2009. This was not the case for other-orphaned or non-orphaned children. Age interacted with orphan status, such that there was a steep rise in psychological distress in the AIDS-orphaned group, but no rise with age amongst other-orphans and non-orphans. Conclusions: Negative mental health outcomes amongst AIDS-orphaned children are maintained and worsen over a 4-year period. It is important that psychosocial support programmes are sustained, and focus on youth as well as young children.